Method for electro-catalytic full-decomposition of seawater by using double-site MOF-based catalyst and application of double-site MOF-based catalyst
By using a two-site MOF-based catalyst as a double-position electrode in seawater electrolysis, the problems of high overpotential and poor stability in seawater electrolysis are solved, and efficient and stable seawater electrolysis is achieved, and chlorine corrosion is avoided.
Patent Information
- Application Number
- CN202510051454.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing transition metal catalysts have problems such as high overpotential, poor stability and unresisting seawater corrosion in seawater electrolysis, resulting in low seawater electrolysis efficiency.
A two-site MOF-based catalyst was used to assemble a flow-type electrolytic cell by using ZIF-L with a large specific surface area as a sacrificial template, and the two-site MOF-based catalyst was used as an anode and a cathode to conduct an electrocatalytic full-resolved seawater reaction.
It has achieved efficient electrocatalytic complete seawater removal in alkaline seawater, improved catalytic efficiency and stability, avoided chlorine corrosion in seawater, and extended the long-term stability of the catalyst.
Smart Images

Figure CN119776877A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water electrolysis, and in particular relates to a method and application of electrocatalytic complete decomposition of seawater using a dual-site MOF-based catalyst. Background Art
[0002] At present, hydrogen production by water electrolysis is one of the important ways to achieve the dual carbon goals. Its reaction process includes two key half-reactions: oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). However, due to the slow kinetics of water splitting reaction, this greatly limits its industrial application process. Therefore, electrocatalysts play a vital role in energy conversion technology. Precious metal-based catalysts (such as Pt, and ) are commonly used as catalysts in industrial water splitting production, but the limited reserves and high costs of these precious metals have hindered their large-scale promotion.
[0003] In order to solve this problem, the development of low-cost and efficient transition metal-based OER and HER electrocatalysts has important research value and practical significance. In reality, due to the scarcity of fresh water resources, the abundance of seawater resources makes seawater electrolysis have good prospects. Seawater electrolysis, like water splitting, mainly includes two anode OER and cathode HER half-reactions. However, in the seawater environment, high concentrations of chloride ions, mainly from sodium chloride and potassium chloride, can lead to the anode side reaction of chlorine evolution reaction (CER) and severe electrode corrosion. OER is kinetically sluggish than CER involving two electrons, so CER in seawater may compete with OER at the anode, reducing the overall efficiency of seawater electrolysis.
[0004] Among the developed catalysts, transition metal phosphides have attracted widespread attention due to their high intrinsic activity. Phosphorus in metal phosphides has two functions. On the one hand, P can capture protons as an alkaline site to promote the adsorption of hydrogen. On the other hand, it can change the electron density of surrounding (especially metal) atoms by providing electrons to adjust their adsorption performance. In addition, by doping other metals on phosphides to form heterogeneous structures, the electronic structure of metal active sites can be more effectively adjusted to improve catalytic performance. Doping with Lewis acid layers can also promote OH - adsorption, which can enhance mass transfer and achieve Cl rejection -The presence of phosphate groups produced by P oxidation can further effectively avoid chlorine corrosion in seawater and extend the long-term stability of the catalyst. MOF has the advantages of low cost, high specific surface area, adjustable pore size and structure, and is an ideal material or precursor for water splitting electrocatalysts.
[0005] In order to solve the above technical problems, the present invention designs a method and application of electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst. Summary of the invention
[0006] The present invention provides a method and application of electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst, aiming to solve the technical problems of high overpotential, poor stability and seawater corrosion resistance of existing transition metal catalysts. The present invention uses ZIF-L with a large specific surface area as a sacrificial template to make the catalyst have more active sites. A flow-type electrolytic cell is assembled, and the prepared electrocatalyst is used as both an anode and a cathode to perform an electrocatalytic decomposition reaction of seawater in alkaline seawater, which has high catalytic efficiency and stability.
[0007] To achieve the above object, the present invention provides the following technical solution: a method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst, comprising the following steps: S1, pre-treating the nickel foam, quickly adding a 2-methylimidazole aqueous solution to a cobalt nitrate hexahydrate aqueous solution and mixing them evenly to obtain a ZIF-L (Co) solution, placing the pre-treated nickel foam into the ZIF-L (Co) solution, stirring for reaction, taking out and rinsing off the unreacted ZIF-L (Co) residual liquid, and placing in a vacuum drying oven for drying to obtain a nickel foam with a ZIF-L (Co) precursor grown thereon; S2, deionized water and anhydrous ethanol are mixed to form a mixed solvent, sodium tungstate is dissolved in the mixed solvent to obtain a sodium tungstate solution, the ZIF-L (Co) precursor foam nickel obtained in step S1 is immersed in the sodium tungstate solution, taken out after etching, rinsed with water and placed in a vacuum drying oven to obtain a nickel foam with WO attached thereto. 4 2- / Co(OH) 2 Intermediate nickel foam; S3, the WO obtained in step S2 is 4 2- / Co(OH) 2 The intermediate nickel foam and phosphorus source are placed in a tubular furnace and subjected to high-temperature phosphating in a protective atmosphere. After being kept warm for a period of time, the mixture is naturally cooled to room temperature to obtain a dual-site MOF-based catalyst. S4, assembling a flow-type electrolytic cell, using the dual-site MOF-based catalyst obtained in step S3 as both the anode and cathode of the flow-type electrolytic cell, using potassium hydroxide solution or alkaline seawater solution as the electrolyte, applying voltage to the electrolytic cell to perform an electrocatalytic reaction, an oxygen evolution reaction occurs at the anode to produce oxygen, and a hydrogen evolution reaction occurs at the cathode to produce hydrogen.
[0008] Based on the above technical solution, in step S1, the step of pretreating the nickel foam includes: placing the nickel foam in hydrochloric acid solution, deionized water and ethanol solution in sequence for ultrasonic treatment, and then placing it in a vacuum drying oven for drying to obtain the pretreated nickel foam.
[0009] Based on the above technical solution, the size of the nickel foam is 30mm*20mm*1.6mm, and the concentration of the hydrochloric acid solution is 2~3mol·L -1 The ultrasonic time of hydrochloric acid is 15~20min, the ultrasonic time of deionized water is 10~15min, and the ultrasonic time of ethanol solution is 5~10min.
[0010] Based on the above technical solution, in step S1, the concentration of the 2-methylimidazole aqueous solution is 0.4 mol·L -1 The concentration of the cobalt nitrate hexahydrate aqueous solution is 0.05 mol·L -1 The volume ratio of 2-methylimidazole aqueous solution and cobalt nitrate hexahydrate aqueous solution is 1:1, and the stirring reaction time is 3~4h.
[0011] Based on the above technical solution, in step S2, the volume ratio of deionized water and anhydrous ethanol in the mixed solvent is 4:1, and the concentration of the sodium tungstate solution is 0.02 mol·L -1 The etching time is 10~15min and the etching temperature is 85℃.
[0012] On the basis of the above technical solution, in step S3, the phosphorus source is sodium hypophosphite powder, the mass ratio of sodium hypophosphite is 0.3-0.4 g, the sodium hypophosphite and the intermediate nickel foam are placed in two porcelain boats respectively, the sodium hypophosphite is placed on the upstream side, the catalyst is placed on the downstream side, the protective atmosphere is nitrogen or argon, the high temperature phosphating temperature is 300-350°C, and the heating rate of the tubular furnace is 2-3°C·min -1 , the insulation time is 2~3h.
[0013] Based on the above technical solution, in S1 and S2, the vacuum drying temperature is 60-80°C, and the drying time is 5-12 hours.
[0014] Based on the above technical solution, in step S4, the area of the MOF-based catalyst used in the anode and cathode of the assembled flow-type electrolytic cell is 1×1 cm 2The concentration of the electrolyte potassium hydroxide solution is 1 mol·L -1 The concentration of potassium hydroxide solution in alkaline seawater is 1 mol·L -1 , the applied voltage range is 1V~2V.
[0015] In a second aspect, the present invention provides a dual-site MOF-based catalyst, which is prepared according to the method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst as described in any one of the above embodiments.
[0016] In a third aspect, the present invention provides an application of a method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to any one of the above embodiments in electrocatalytic decomposition of seawater.
[0017] Compared with the related art, the beneficial effects of the present invention are as follows: The present invention provides a method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst. The synthesized catalyst has a two-dimensional nanosheet morphology and can be evenly loaded on a conductive substrate nickel foam. The catalyst is in situ grown and firmly bonded to the substrate, avoiding problems such as weak conductivity caused by drip coating with an adhesive. The doping of the [WO] group can provide a Lewis acid layer to enhance the OH - adsorption, promoting the OER reaction and repelling Cl - On the other hand, the formation of a heterostructure with CoP can regulate the electronic structure of the Co active site. At the same time, W is hydrophilic and can more effectively capture water molecules as the active site of HER. The presence of phosphate groups produced by the oxidation of P in CoP can further effectively avoid chlorine corrosion in seawater and extend the long-term stability of the catalyst. When the dual-site MOF-based catalyst is used as a working electrode in the electrocatalytic complete decomposition of seawater, it has high catalytic efficiency and cyclic stability for both HER and OER. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only one embodiment of the present invention, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0019] Figure 1 It is a flow chart of the method for electrocatalytic complete decomposition of seawater using a dual-site MOF-based catalyst provided by the present invention.
[0020] Figure 2 This is a scanning electron microscope image of the 0.6WO-CoP@NF catalyst prepared in Example 1 of the present invention.
[0021] Figure 3 It is a transmission electron microscope image of 0.6WO-CoP grown on the 0.6WO-CoP@NF catalyst prepared in Example 1 of the present invention.
[0022] Figure 4 This is an energy dispersive X-ray spectrum of the 0.6WO-CoP@NF catalyst prepared in Example 1 of the present invention.
[0023] Figure 5 It is the X-ray diffraction spectrum of the 0.6WO-CoP@NF catalyst in Example 1 of the present invention and the CoP@NF catalyst in Comparative Example 1.
[0024] Figure 6 It is the X-ray photoelectron energy spectrum of the 0.6WO-CoP@NF catalyst in Example 1 of the present invention and the CoP@NF in Comparative Example 1.
[0025] Figure 7 It is a test diagram of the oxygen evolution reaction performance of Comparative Examples 1-3 of the present invention.
[0026] Figure 8 It is a test diagram of the hydrogen evolution reaction performance of Comparative Examples 1-3 of the present invention.
[0027] Fig. 9 It is a scatter plot of the oxygen evolution reaction stability of Comparative Examples 1 and 3 of the present invention.
[0028] Fig.10 It is the polarization scatter diagram of the fully decomposed water measured in Example 1 and Example 2 of the present invention.
[0029] Fig.11 It is a scatter plot of the complete water decomposition stability measured in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with the accompanying drawings and examples: Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0031] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0032] In the description of the present invention, it should be understood that the terms "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0033] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0034] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0035] The present invention provides a method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst, comprising the following steps: S1, pre-treating the nickel foam, quickly adding a 2-methylimidazole aqueous solution to a cobalt nitrate hexahydrate aqueous solution and mixing them evenly to obtain a ZIF-L (Co) solution, placing the pre-treated nickel foam into the ZIF-L (Co) solution, stirring for reaction, taking out and rinsing off the unreacted ZIF-L (Co) residual liquid, and placing in a vacuum drying oven for drying to obtain a nickel foam with a ZIF-L (Co) precursor grown thereon; S2, deionized water and anhydrous ethanol are mixed to form a mixed solvent, sodium tungstate is dissolved in the mixed solvent to obtain a sodium tungstate solution, the ZIF-L (Co) precursor foam nickel obtained in step S1 is immersed in the sodium tungstate solution, taken out after etching, rinsed with water and placed in a vacuum drying oven to obtain a nickel foam with WO attached thereto. 4 2- / Co(OH) 2 Intermediate nickel foam; S3, the WO obtained in step S2 is 4 2- / Co(OH) 2 The intermediate nickel foam and phosphorus source are placed in a tubular furnace and subjected to high-temperature phosphating in a protective atmosphere. After being kept warm for a period of time, the mixture is naturally cooled to room temperature to obtain a dual-site MOF-based catalyst. S4, assembling a flow-type electrolytic cell, using the dual-site MOF-based catalyst obtained in step S3 as both the anode and cathode of the flow-type electrolytic cell, using potassium hydroxide solution or alkaline seawater solution as the electrolyte, applying voltage to the electrolytic cell to perform an electrocatalytic reaction, an oxygen evolution reaction occurs at the anode to produce oxygen, and a hydrogen evolution reaction occurs at the cathode to produce hydrogen.
[0036] Based on the above technical solution, in step S1, the step of pretreating the nickel foam includes: placing the nickel foam in hydrochloric acid solution, deionized water and ethanol solution in sequence for ultrasonic treatment, and then placing it in a vacuum drying oven for drying to obtain the pretreated nickel foam.
[0037] Based on the above technical solution, the size of the nickel foam is 30mm*20mm*1.6mm, and the concentration of the hydrochloric acid solution is 2~3mol·L -1 The ultrasonic time of hydrochloric acid is 15-20 min, the ultrasonic time of deionized water is 10-15 min, and the ultrasonic time of ethanol solution is 5-10 min. Preferably, the concentration of hydrochloric acid solution is 3 mol·L -1 The ultrasonic time of hydrochloric acid was 15 min, the ultrasonic time of deionized water was 10 min, and the ultrasonic time of ethanol solution was 5 min.
[0038] Based on the above technical solution, in step S1, the concentration of the 2-methylimidazole aqueous solution is 0.4 mol·L -1 The concentration of the cobalt nitrate hexahydrate aqueous solution is 0.05 mol·L -1 The volume ratio of the 2-methylimidazole aqueous solution to the cobalt nitrate hexahydrate aqueous solution is 1:1, and the stirring reaction time is 3 to 4 hours. Preferably, the stirring reaction time is 4 hours.
[0039] Based on the above technical solution, in step S2, the volume ratio of deionized water and anhydrous ethanol in the mixed solvent is 4:1, and the concentration of the sodium tungstate solution is 0.02 mol·L -1 , the etching time is 10-15 min, and the etching temperature is 85° C. Preferably, the etching time is 15 min.
[0040] On the basis of the above technical solution, in step S3, the phosphorus source is sodium hypophosphite powder, the mass ratio of sodium hypophosphite is 0.3-0.4 g, the sodium hypophosphite and the intermediate nickel foam are placed in two porcelain boats respectively, the sodium hypophosphite is placed on the upstream side, the catalyst is placed on the downstream side, the protective atmosphere is nitrogen or argon, the high temperature phosphating temperature is 300-350°C, and the heating rate of the tubular furnace is 2-3°C·min -1 , the holding time is 2-3h. Preferably, the mass ratio of sodium hypophosphite is 0.4g, the high temperature phosphating temperature is 350℃, and the heating rate of the tube furnace is 2℃·min -1 , the insulation time is 2h.
[0041] Based on the above technical solution, in S1 and S2, the vacuum drying temperature is 60-80°C, and the drying time is 5-12 hours. Preferably, the vacuum drying temperature is 60°C, and the drying time is 6 hours.
[0042] Based on the above technical solution, in step S4, the area of the MOF-based catalyst used in the anode and cathode of the assembled flow-type electrolytic cell is 1×1 cm 2 The concentration of the electrolyte potassium hydroxide solution is 1 mol·L -1 The concentration of potassium hydroxide solution in alkaline seawater is 1 mol·L -1 , the applied voltage range is 1V~2V.
[0043] In a second aspect, the present invention provides a dual-site MOF-based catalyst, which is prepared according to the method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst as described in any one of the above embodiments.
[0044] In a third aspect, the present invention provides an application of a method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to any one of the above embodiments in electrocatalytic decomposition of seawater.
[0045] Example 1 Combination Figure 1 As shown, the embodiment of the present disclosure provides a method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst, comprising the following steps: S1. Place nickel foams with sizes of 30 mm*20 mm*1.6 mm in 3 mol·L -1 The pretreated nickel foam was treated with ultrasonic treatment in hydrochloric acid solution for 15 min, in deionized water for 10 min, and in anhydrous ethanol solution for 5 min, and then placed in a vacuum drying oven at 60 °C for 6 h to obtain pretreated nickel foam. 40 ml of 0.4 mol·L -1 The 2-methylimidazole aqueous solution was quickly added into 40 ml of 0.05 mol·L cobalt nitrate hexahydrate aqueous solution and mixed evenly to obtain a ZIF-L (Co) solution, and the pretreated nickel foam was placed into the ZIF-L (Co) solution, stirred for reaction for 4 h, and then taken out and the unreacted ZIF-L (Co) residual liquid was rinsed off with deionized water, and then placed in a vacuum drying oven at 60 ° C for 6 h to obtain a nickel foam with a ZIF-L (Co) precursor grown thereon; S2, 80 mL of deionized water and 20 mL of anhydrous ethanol were mixed to form a mixed solvent, 0.6 g of sodium tungstate was dissolved in the mixed solvent to obtain a sodium tungstate solution, the ZIF-L (Co) precursor foam nickel obtained in step S1 was immersed in the sodium tungstate solution, etched at 85 ° C for 15 min, then taken out, rinsed with deionized water for several times, and placed in a vacuum drying oven at 60 ° C for 6 h to obtain a WO attached nickel foam. 4 2- / Co(OH) 2 Intermediate nickel foam; S3, the WO obtained in step S2 4 2- / Co(OH) 2 The intermediate nickel foam and 0.4 g sodium hypophosphite were placed in a tube furnace, with the sodium hypophosphite placed on the upstream side and the intermediate placed on the downstream side. The tube furnace was heated at 2 °C min in a nitrogen atmosphere. -1 The heating rate was raised to 350 °C for high-temperature phosphating, and after keeping the temperature for 2 h, it was naturally cooled to room temperature to obtain the dual-site MOF-based catalyst 0.6WO-CoP@NF. S4. Assemble a flow-type electrolytic cell, use the dual-site MOF-based catalyst obtained in step S3 as both the anode and cathode of the flow-type electrolytic cell, add 1 mol of potassium hydroxide into 1 L of natural seawater to dissolve to obtain alkaline seawater, use the alkaline seawater as the electrolyte, apply a voltage from 1 V to 2 V to the electrolytic cell, and perform an electrocatalytic reaction. An oxygen evolution reaction occurs at the anode to produce oxygen, and a hydrogen evolution reaction occurs at the cathode to produce hydrogen.
[0046] Example 2 The method of this embodiment is the same as that of embodiment 1, and the same parts are omitted. The difference from embodiment 1 is that in this embodiment, 1 mol·L -1 Potassium hydroxide solution is the electrolyte.
[0047] Comparative Example 1 The method of this embodiment is the same as that of Example 1, and the same parts are omitted. The difference from Example 1 is that, in this embodiment, a three-electrode system is adopted, a dual-site MOF-based catalyst is used as a working electrode, a high-purity graphite rod is used as a counter electrode, and Ag / AgCl is used as a reference electrode. The electrocatalytic reaction is carried out in an electrolyte, and the masses of sodium tungstate are 0, 0.3, 0.6, and 0.9 g, respectively.
[0048] Comparative Example 2 The method of this embodiment is the same as that of Comparative Example 1, and the same parts are omitted. The difference from Comparative Example 1 is that, in this embodiment, 1 mol potassium hydroxide and 0.5 mol sodium chloride are added to 1 L of deionized water to dissolve to obtain simulated seawater, and the simulated seawater is used as the electrolyte.
[0049] Comparative Example 3 The method of this embodiment is the same as that of Comparative Example 1, and the same parts are omitted. The difference from Comparative Example 1 is that, in this embodiment, 1 mol of potassium hydroxide is added to 1 L of natural seawater to dissolve to obtain alkaline seawater, and the alkaline seawater is used as the electrolyte.
[0050] Figure 2 This is a scanning electron microscope image of the 0.6WO-CoP@NF catalyst prepared in Example 1 of the present invention. It can be seen that it presents the morphology of nanosheets. The nanosheets have more lateral dimensions and abundant unsaturated metal active sites, which are conducive to the binding of water molecules and improve the electrocatalytic performance.
[0051] Figure 3 From the transmission electron microscopy image of 0.6WO-CoP grown on the 0.6WO-CoP@NF catalyst prepared in Example 1 of the present invention, it can be seen that the interplanar spacing of CoP is reduced by about 0.003nm, which can be attributed to the generation of lattice stress caused by the doping of [WO] groups. The reduction in lattice spacing indicates the successful doping of [WO] groups.
[0052] Figure 4 This is an energy dispersive X-ray spectrum of the 0.6WO-CoP@NF catalyst prepared in Example 1 of the present invention. It can be seen that the elements P, Co, O, W, and C in the 0.6WO-CoP catalyst are evenly distributed.
[0053] Figure 5 It is the X-ray diffraction spectra of the 0.6WO-CoP@NF catalyst in Example 1 of the present invention and the CoP@NF catalyst in Comparative Example 1. It can be seen that the crystal structures of the two samples can correspond well to the diffraction peaks of the standard CoP card (CoP#65-2593), indicating that the main crystal phase of the catalyst is CoP, which is consistent with the transmission electron microscopy results.
[0054] Figure 6 is the X-ray photoelectron spectrum of the 0.6WO-CoP@NF catalyst in Example 1 of the present invention and the CoP@NF in Comparative Example 1. Figure 6 In a, we can see that the high-resolution Co 2p spectrum shows that it belongs to Co 2p 3 / 2 and Co 2p 1 / 2 The binding energy of the Co-P bond is the characteristic peaks of 778.61eV and 793.59eV, and the peaks belonging to the Co 2p 3 / 2 and Co 2p 1 / 2 The binding energy of the Co-O bond is the characteristic peaks at 782.19 eV and 798.21 eV, while the peaks at 786.13 eV and 802.77 eV correspond to two satellite peaks. In addition, the Co 2p spectrum of 0.6WO-CoP@NF shows a slight positive shift compared with CoP@NF, the oxidation state of Co slightly increases, and the electron transfer from Co occurs, which can indicate the successful doping of [WO] groups. Figure 6 b is the high-resolution w 4f spectrum, where w 4f 7 / 2 and w4f 5 / 2 36.12eV and 38.4eV respectively, corresponding to the WO bond. Figure 6 From the X-ray photoelectron spectrum of P 2p of c, it can be seen that the peaks at 129.6eV and 130.4eV belong to 2p 3 / 2 and 2p 1 / 2 The peak at 134.20 eV comes from the Co-P bond, while the peak at 134.20 eV comes from the oxidation state of P.
[0055] Figure 7 It is a test diagram of the oxygen evolution reaction performance of Comparative Examples 1-3 of the present invention. Figure 7 a is the OER polarization curve of the catalyst with different tungsten contents in Comparative Example 1. Figure 7 It can be seen from a that the overpotential of 0.6WO-CoP@NF is the smallest at 100 mA cm -2 At a current density of , the overpotential is 335mV. Figure 7 b is the Tafel slope diagram of the catalysts with different tungsten contents in comparative example 1, from which it can be seen that 0.6WO-CoP@NF has the smallest Tafel slope of 106.4 mV·dec -1 , which indicates that 0.6WO-CoP@NF has faster OER kinetics. Figure 7 c is the electrochemical impedance spectrum of the catalyst with different tungsten contents in comparative example 1, from which it can be seen that the charge transfer resistance of the 0.6WO-CoP@NF catalyst is smaller, proving that it has higher conductivity and faster charge transfer rate in the OER process. Figure 7 d is the OER polarization curve of 0.6WO-CoP@NF catalyst in Examples 1-3. It can be seen that 0.6WO-CoP@NF has a high OER polarization rate in simulated seawater and 1 mol·L -1 There is almost no difference in the OER activity in potassium hydroxide solution. In alkaline seawater, there is a certain loss of activity due to electrode poisoning caused by natural seawater pollutants. Even in this case, the 0.6WO-CoP@NF catalyst can still provide 100 mA cm at 370 mV. -2 The current density of 0.6WO-CoP@NF catalyst was shown to be excellent for chlorine removal.
[0056] Figure 8 It is a test diagram of the hydrogen evolution reaction performance of Comparative Examples 1-3 of the present invention. Figure 8 a is the HER polarization curve of the catalyst with different tungsten contents in Comparative Example 1. Figure 8 It can be seen from a that the overpotential of 0.6WO-CoP@NF is the smallest at 10 mA cm -2 At a current density of , the overpotential is 66 mV. Figure 8 b summarizes the overpotentials of catalyst electrodes with different tungsten contents at different currents in HER. It can be seen that 0.6WO-CoP@NF has the best reaction activity in HER. Figure 8 c is the Tafel slope diagram of the catalysts with different tungsten contents in comparative example 1, from which it can be seen that 0.6WO-CoP@NF has the smallest Tafel slope of 74.4 mV·dec -1, which indicates that 0.6WO-CoP@NF has faster hydrogen evolution kinetics. Figure 8 d is the HER polarization curve of the 0.6WO-CoP@NF catalyst in Examples 1-3. It can be seen that the 0.6WO-CoP@NF catalyst has a high HER polarization rate in simulated seawater and 1 mol·L -1 There is almost no difference in HER compared with that in KOH solution. In alkaline seawater, there is a certain loss of activity due to electrode poisoning caused by natural seawater pollutants. Even in this case, the 0.6WO-CoP@NF catalyst can still provide 100 mA cm at 185 mV. -2 The current density of 0.6WO-CoP@NF catalyst was shown to be excellent for chlorine removal.
[0057] Fig. 9 The OER stability scatter plot of 0.6WO-CoP@NF catalyst measured by chronopotentiometry in Comparative Examples 1 and 3 of the present invention shows that at 100 mA·cm -2 At a current density of 1 mol·L -1 It can be kept in potassium hydroxide solution and alkaline seawater for 100 hours, proving its good stability.
[0058] Fig.10 The polarization curves of fully decomposed water measured in Example 1 and Example 2 of the present invention show that at 60°C, 1 mol·L -1 In potassium hydroxide electrolyte, only 1.59V is required to reach 100mA·cm -2 The current density is 2.33 W, and the polarization curve in alkaline seawater shows that the catalyst still has good performance.
[0059] Fig.11 The scatter plot of the stability of water splitting measured by chronopotentiometry in Example 1 of the present invention shows that at 100 mA·cm -2 It can operate stably for 250 hours at a current density without obvious activity decay.
[0060] The present invention is described above by way of examples, but the present invention is not limited to the above specific embodiments, and any changes or modifications made based on the present invention belong to the scope of protection claimed by the present invention.
Claims
1. A method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst, characterized in that: The following steps are involved: S1, pre-treating the nickel foam, quickly adding a 2-methylimidazole aqueous solution to a cobalt nitrate hexahydrate aqueous solution and mixing them evenly to obtain a ZIF-L (Co) solution, placing the pre-treated nickel foam into the ZIF-L (Co) solution, stirring for reaction, taking out and rinsing off the unreacted ZIF-L (Co) residual liquid, and placing in a vacuum drying oven for drying to obtain a nickel foam with a ZIF-L (Co) precursor grown thereon; S2, deionized water and anhydrous ethanol are mixed to form a mixed solvent, sodium tungstate is dissolved in the mixed solvent to obtain a sodium tungstate solution, the ZIF-L (Co) precursor foam nickel obtained in step S1 is immersed in the sodium tungstate solution, taken out after etching, rinsed with water and placed in a vacuum drying oven to obtain a WO4 2- / Co(OH)2 intermediate nickel foam; S3, the WO4 obtained in step S2 2- The intermediate nickel foam and phosphorus source of / Co(OH)2 were placed in a tubular furnace for high-temperature phosphating in a protective atmosphere, and then naturally cooled to room temperature after a period of heat preservation to obtain a dual-site MOF-based catalyst; S4, assembling a flow-type electrolytic cell, using the dual-site MOF-based catalyst obtained in step S3 as both the anode and cathode of the flow-type electrolytic cell, using potassium hydroxide solution or alkaline seawater solution as the electrolyte, applying voltage to the electrolytic cell to perform an electrocatalytic reaction, an oxygen evolution reaction occurs at the anode to produce oxygen, and a hydrogen evolution reaction occurs at the cathode to produce hydrogen.
2. The method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to claim 1, characterized in that: In step S1, the step of pre-treating the nickel foam comprises: placing the nickel foam in a hydrochloric acid solution, a deionized water solution and an ethanol solution in sequence for ultrasonic treatment, and then placing the nickel foam in a vacuum drying oven for drying to obtain the pre-treated nickel foam.
3. The method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to claim 2, characterized in that: The size of the nickel foam is 30mm*20mm*1.6mm, and the concentration of the hydrochloric acid solution is 2~3mol·L -1 The ultrasonic time of hydrochloric acid is 15~20min, the ultrasonic time of deionized water is 10~15min, and the ultrasonic time of ethanol solution is 5~10min.
4. The method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to claim 1, characterized in that: In step S1, the concentration of the 2-methylimidazole aqueous solution is 0.4 mol·L -1 The concentration of the cobalt nitrate hexahydrate aqueous solution is 0.05 mol·L -1 The volume ratio of 2-methylimidazole aqueous solution and cobalt nitrate hexahydrate aqueous solution is 1:1, and the stirring reaction time is 3~4h.
5. The method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to claim 1, characterized in that: In step S2, the volume ratio of deionized water and anhydrous ethanol in the mixed solvent is 4:1, and the concentration of the sodium tungstate solution is 0.02 mol·L -1 The etching time is 10~15min and the etching temperature is 85℃.
6. The method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to claim 1, characterized in that: In step S3, the phosphorus source is sodium hypophosphite powder, the mass ratio of sodium hypophosphite is 0.3-0.4 g, the sodium hypophosphite and the intermediate nickel foam are placed in two porcelain boats respectively, the sodium hypophosphite is placed on the upstream side, and the catalyst is placed on the downstream side, the protective atmosphere is nitrogen or argon, the high temperature phosphating temperature is 300-350°C, and the heating rate of the tubular furnace is 2-3°C·min -1 , the insulation time is 2~3h.
7. The method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to claim 1, characterized in that: In S1 and S2, the vacuum drying temperature is 60-80° C., and the drying time is 5-12 hours.
8. The method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to claim 1, characterized in that: In step S4, the area of the MOF-based catalyst used in the anode and cathode of the assembled flow-type electrolytic cell is 1×1 cm 2 The concentration of the electrolyte potassium hydroxide solution is 1 mol·L -1 The concentration of potassium hydroxide solution in alkaline seawater is 1 mol·L -1 , the applied voltage range is 1V~2V.
9. A dual-site MOF-based catalyst, characterized in that: It is prepared by the method for electrocatalytic decomposition of seawater using a dual-site MOF-based catalyst according to any one of claims 1 to 8.
10. Use of the method for electrocatalytic complete seawater decomposition using a dual-site MOF-based catalyst according to any one of claims 1 to 8 in electrocatalytic complete seawater decomposition.
Citation Information
Patent Citations
Preparation of three-dimensional hollow flower-shaped cobalt tungstate supercapacitor material derived based on metal organic framework
CN112038115A
Mo-Co-O-ZIF-67 / NF nano-catalyst as well as preparation method and application thereof
CN117867563A
Preparation method and application of cobalt-based trimetal hollow cubic structure electrocatalyst
CN118374829A
MOF-derived tungsten-doped ferronickel phosphide difunctional electrocatalyst and preparation method thereof
CN118745580A
Modified metal-organic framework (MOF) compositions, process of making and process of use thereof
WO2021202565A1